Respuesta :

Answer:

11 1 1/2 - 2 2/3 = 8.4

Step-by-step explanation:

11 and add 1 is 12 add the half and 12.5 - 2.6 = 8.4

For this case we must simplify the following expression:

[tex]11 \frac {1} {2} -2 \frac {2} {3}[/tex]

So:

[tex]11 \frac {1} {2} = \frac {2 * 11 + 1} {2} = \frac {22 + 1} {2} = \frac {23} {2}\\2 \frac {2} {3} = \frac {3 * 2 + 2} {3} = \frac {6 + 2} {3} = \frac {8} {3}[/tex]

Rewriting the expression:

[tex]\frac {23} {2} - \frac {8} {3} = \frac {3 * 23-2 * 8} {2 * 3} = \frac {69-16} {6} = \frac {53 } {6}[/tex]

Answer:

[tex]\frac {53} {6}=8 \frac{5}{6}[/tex]